Assessment Of Groundwater Quality In Rohtak Municipal Corporation, India: A Zone-Wise Analysis (International Journal of Environmental Sciences, 2024)
Groundwater is a critical resource for domestic, agricultural, and industrial use in India. This is all the more relevant for urban areas like Rohtak. Unplanned urbanisation and inadequate waste management are significant threats to groundwater quality. To assess the physicochemical characteristics of groundwater across six zones of Rohtak Municipal Corporation and evaluate its suitability for drinking by comparing it with Indian and international standards. A cross-sectional study was conducted, collecting secondary data on key water quality parameters of pH, Total Hardness, Fluoride, Total Dissolved Solids, Nitrate, Sulphate, Arsenic and Calcium for all six zones of Rohtak. Data were analysed using descriptive statistics. A one-sample t-test was used to compare the mean values of each parameter against the acceptable limits prescribed by the Bureau of Indian Standards (IS 10500:2012). Visual comparison was done through graphic representations. The analysis highlighted significant contamination in several zones. The parameters of Total Hardness, Total Dissolved Solids (TDS), and Fluoride exceeded the acceptable limits in multiple zones. The Zones V and VI were particularly affected, with Zone VI showing extreme levels of Total Hardness (1720 mg/L) and all zones except Zone IV exceeding the TDS permissible limits. The pH and Nitrate levels were generally within safe limits across all zones. Arsenic was not detected (ND) in any sample. The groundwater in Rohtak Municipal Corporation is contaminated, with several parameters surpassing the desirable limits for drinking water. The spatial variation indicates zones requiring immediate attention. Continuous monitoring, public awareness, and the implementation of robust water treatment solutions are urgently required to safeguard public health.